Pendidikan Kesehatan tentang Pencegahan Penularan Penyakit Coronavirus (COVID-19) pada Masyarakat yang Berdomisili di Wilayah Kerja Puskesmas Malawili, Kabupaten Sorong, Papua Barat - Maria Loihala; E. J Tanamal (Poltekkes Kemenkes Kendari, 2021)
In December 2019 in Wuhan, China, a new type of virus emerged, coronavirus disease (COVID-19), and hit the world including in Sorong regency. An increase in COVID-19 as in July 2020, as many as 380 people without symptoms, 62 close contacts, 8 suspected cases, 70 confirmed cases, 60 patients recovered and 1 patient died. Increasing in the incidence of COVID-19 spread in Aimas sub-district, Mariat sub-district, Salawati sub-district, and Moisegen sub-district. The purpose of this Community Service (Pengabmas) was to increase awareness through the knowledge, attitudes, and abilities of the community in preventing the transmission of COVID-19 in the Puskesmas Malawili work area, Sorong Regency. Total participants were 69 people, data was collected using a questionnaire. Pengabmas methods were lectures and demonstrations, and leaflets are used as media. There was a difference in the total score of the knowledge from the questionnaire before and after being given health education.